2013
DOI: 10.1002/tox.21859
|View full text |Cite
|
Sign up to set email alerts
|

Markers of oxidative stress in hepatopancreas of crayfish (orconectes limosus, raf) experimentally exposed to nanosilver

Abstract: Silver nanoparticles, chemically neutral particles in the size range of 1-100 nm, express strong antimicrobial activity and therefore have a broad range of applications. The increased use of consumer products with nanosilver (nanoAg) may result in its release into the environment, and may particularly affect aquatic systems. The mechanisms of the harmful effects of nanoAg against aquatic organisms are unclear. Therefore, in the present study we investigate the pro-oxidative potential of these nanoparticles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…A number of biochemical biomarkers were studied in Daphnia magna after acute exposure to different pollutants (Jemec et al 2008; Barata et al 2005;Toumi et al 2015;Diamantino et al 2000). The information on biochemical responses in D. magna exposed to different ENPs are still scarce, despite the requirements for risk assessment of the potential impact of ENPs on the aquatic environment (OECD 2004;Dominguez et al 2015;Zou et al 2014;Mwaanga et al 2014;Strużyński et al 2014). The aquatic crustacean D. magna has been recognized as first choice in ecotoxicological tests on nanomaterials (Baun et al 2008;Kahru et al 2008).…”
Section: Responsible Editor: Thomas Hutchinsonmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of biochemical biomarkers were studied in Daphnia magna after acute exposure to different pollutants (Jemec et al 2008; Barata et al 2005;Toumi et al 2015;Diamantino et al 2000). The information on biochemical responses in D. magna exposed to different ENPs are still scarce, despite the requirements for risk assessment of the potential impact of ENPs on the aquatic environment (OECD 2004;Dominguez et al 2015;Zou et al 2014;Mwaanga et al 2014;Strużyński et al 2014). The aquatic crustacean D. magna has been recognized as first choice in ecotoxicological tests on nanomaterials (Baun et al 2008;Kahru et al 2008).…”
Section: Responsible Editor: Thomas Hutchinsonmentioning
confidence: 99%
“…Therefore, implementation of biochemical biomarkers is considered to be a promising tool for ecotoxicological applications as early warning indicators (Strużyński et al 2014;Jemec et al 2008). A number of biochemical biomarkers were studied in Daphnia magna after acute exposure to different pollutants (Jemec et al 2008; Barata et al 2005;Toumi et al 2015;Diamantino et al 2000).…”
Section: Responsible Editor: Thomas Hutchinsonmentioning
confidence: 99%
“…In addition, various animal experimental models have also linked oxidative stress to AgNP-induced cytotoxicity (Eom et al, 2013;Struzynski et al, 2014;Wu and Zhou, 2013). In nanoAg-exposed fish (Scown et al, 2010) and rodents (Rahman et al, 2009) up-regulation of oxidative stress-related genes has been demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…The chemical interaction between AgNPs and the cell membrane of bacteria can be related to the presence of sulphur in proteins, forming preferential sites with AgNPs . Therefore, exposure to AgNPs promotes an increase in the rate of lipid peroxidation and oxidation of the protein due to lesser thiol groupings (-SH) bounded to protein (Strużyński et al, 2014). The reduction of thiol levels and glutathione activity may induce AgNP-exposed organisms to ineffective antioxidant mechanisms against cellular stress mediated by reactive oxygen species (Becaro et al, 2015).…”
Section: Resultsmentioning
confidence: 99%